Describing the scattering of keV protons through graphene - Bühler, Jakob; Roncin, Philippe; Brand, Christian (Frontiers in Chemistry, 2023)
Implementing two-dimensional materials in technological solutions requires fast, economic, and non-destructive tools to ensure efficient characterization. In this context, scattering of keV protons through free-standing graphene was proposed as an analytical tool. Here, we critically evaluate the predicted effects using classical simulations including a description of the lattice's thermal motion and the membrane corrugation via statistical averaging. Our study shows that the zero-point motion of the lattice atoms alone leads to considerable broadening of the signal that is not properly described by thermal averaging of the interaction potential. In combination with the non-negligible probability for introducing defects, it limits the prospect of proton scattering at 5 keV as an analytic tool.